Konflik Perundangan Hak Hadhanah bagi Ibu Non-Muslim di Malaysia - Farah Nabilah Binti Zulfahrizal; Sudirman Suparmin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study examines the considerations made by the Civil Court and the Sharia Court in Malaysia in enforcing the right of children in cases of various religious issues in connection with the 1976 Act to Revise the Law (Marriage and Divorce) (Akta 164). The type of research used is qualitative research with normative jurisprudential methodology related to Malaysian law and Islamic law. The source uses secondary data, which combines documentary studies from the Civil Court and Sharia Court decisions. The researchers found that the right to have children was given priority to women because women's fitrah was full of affection and tenderness in raising children. In the preliminary formulation, the researchers found that the courts granted the right to a gift based on certain factors, such as age issues, child wishes, parents' wishes and religion, family backgrounds, and even relatives. The researcher also notes that the decision to determine the religion of a child under the age of 18 is under the supervision of a parent or guardian, but this is not a fixed decision. For this case, the decision of the power of the judge in the court will be used as the determination of the right of the child.